2018
DOI: 10.1002/jeab.457
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative responding in rats maintained by fixed‐ and variable‐ratio schedules

Abstract: The present study investigated the effects of fixed-ratio (FR) and variable-ratio (VR) reinforcement schedules on patterns of cooperative responding in pairs of rats. Experiment 1 arranged FR 1, FR 10, and VR 10 schedules to establish cooperative responding (water delivery depended on the joint responding of two rats). Cooperative response rates and proportions were higher under intermittent schedules than under continuous reinforcement. The FR 10 schedule generated a break-and-run pattern, whereas the VR 10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 31 publications
5
34
1
5
Order By: Relevance
“…8). The FR control procedure replicated previous findings for variable-interval schedules (Tan and Hackenberg, 2016;de Carvalho et al, 2018de Carvalho et al, , 2019 and from experiments that showed higher rates of coordination in mutual contingencies than in independent Note. Panel A: Coordinated rates for each dyad in the FR 9 and Control conditions.…”
Section: Discussionsupporting
confidence: 82%
“…8). The FR control procedure replicated previous findings for variable-interval schedules (Tan and Hackenberg, 2016;de Carvalho et al, 2018de Carvalho et al, , 2019 and from experiments that showed higher rates of coordination in mutual contingencies than in independent Note. Panel A: Coordinated rates for each dyad in the FR 9 and Control conditions.…”
Section: Discussionsupporting
confidence: 82%
“…O estudo experimental da cooperação com inspiração em procedimentos e conceitos da análise do comportamento tem produzido interessantes estudos experimentais, como análises do mutualismo e coordenação em ratos ou pombos (Carvalho et al, 2018;Tan & Hackenberg, 2016;Velasco, Benvenuti, Sampaio, & Tomanari, 2017), reciprocidade (Ribes & Pulido, 2015) e altruísmo (Locey, Safin, & Raclin, 2013). A noção de cooperação desses estudos, ainda que nem sempre explicitada, envolve reforçadores que são interdependentes, e o comportamento de um participante acaba por se tornar estímulo discriminativo para outro, consistente com a definição sugerida por Schmitt (1998).…”
Section: Introductionunclassified
“…Assim, a cooperação pode ser vista como uma relação entre dois ou mais indivíduos que ocorre em um contexto particular de contingências e especificam qual resposta deve ser emitida naquele contexto e o critério para que essa resposta seja reforçada. Com essa definição, nota-se que, ao estudar o fenômeno cooperação, o pesquisador poderá investigar diversos temas relacionados à cooperação, como, por exemplo, o mutualismo (de Carvalho, et al, 2018;Tan & Hackenberg, 2016;Velasco, Benvenuti, Sampaio, & Tomanari, 2017), a reciprocidade (Ribes-Iñesta et al, 2010;Ribes & Pulido, 2015), o altruísmo e também o altruísmo parcial (Avalos, Ribes-Iñesta, Ortiz, & Serna, 2015).…”
Section: Análise Experimental Da Cooperaçãounclassified
“…Tradicionalmente, a análise experimental da cooperação utiliza uma metodologia em que reforços são distribuídos em função de classes topográficas de coordenação de respostas entre dois ou mais indivíduos (e.g., Azrin & Lindsley, 1956;Brotsky & Thomas, 1967;de Carvalho et al, 2018;Hake & Vukelich, 1972;Lindsley, 1966;Schmitt & Marwell, 1968, Tan & Hackenberg, 2016Toledo & Benvenuti, 2015;Velasco, Benvenuti, Sampaio, & Tomanari, 2017). Ao atingir o critério estabelecido pelo experimentador sobre como as respostas devem ser coordenadas, as respostas de todos os indivíduos envolvidos na contingência são reforçadas (Hake & Vukelich, 1972;Schmitt, 1998).…”
Section: Introductionunclassified
See 1 more Smart Citation